MOTIVATIONAL ASPECTS OF THE INNOVATIVE ACTIVITIES OF ENTERPRISES - M. Omelchenko (Вестник университета)
The problems of development of innovative activity are in modern transformation terms is lighted up in the article. A necessity of strengthening of motivational influence on a personnel with the purpose of activation of innovative activity is grounded. The personnel management system includes eleven interconnected subsystems of external and internal environment which provide effective management, motivation and development of labor resources. The development of new types of products and the improvement of existing production are provided precisely because of the high innovative activity of the personnel which is the product of stimulating labor in the sphere of innovative activity.